K. SCHMITT’S THEORY OF PARTISAN: SOCIO-POLITICAL EVENTUALITY OF PARTISAN - M. P. Ostromenskij (Vestnik MGIMO-Universiteta, 2016)
Eventual socio-political conditions of the appearance of a partisan are considered. It is shown that the appearance of the partisan becomes possible when the socio-political uncertainty in the state and social anomie in society caused serious set into question the legitimacy of the sovereign. In such circumstances, falling value of public institutions, the rule of law and the rules of the routine, but the role of the individual and adopt independent decisions, in each case, increases. And increasing the area of independent ad hoc decisions. Such conditions arise in the occupied territory, especially in a situation of the continuing war. Besides, here indigenous people without taking any illegal actions, from the point of view of both clashing sovereigns, it is struck in the rights. All this makes a real opportunity to show the political subjectivity of the citizen, even with low social status. The behavior of the occupied population can follow three models: expectations of the solution of the conflict between sovereigns and the subsequent acceptance of its results as due - absolute majority population, the active help to the occupying sovereign for the purpose of the statement new political - the collaborator, active opposition of the occupying authority for the purpose of return former political - the partisan.